2020
DOI: 10.1016/j.healun.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and clinical characteristics of heart transplant recipients during the 2019 coronavirus outbreak in Wuhan, China: A descriptive survey report

Abstract: BACKGROUND: The epidemiologic and clinical characteristics of heart transplant (HTx) recipients during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic remains unclear. We studied the characteristics of HTx recipients from December 20, 2019, to February 25, 2020, in an effort to understand their risk and outcomes. METHODS: All accessible HTx recipients were included in this single-center retrospective study. We collected information on the recipients using a web-based questionnaire as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 36 publications
2
50
0
13
Order By: Relevance
“…5 Additionally, a recent report followed 87 heart transplant recipients in Hubei, finding a low rate of SARS-CoV-2 infection with no severe cases of COVID-19 among them. 19 Interestingly, SOT recipients similarly did not appear to be at particularly increased risk of adverse outcomes in past novel…”
Section: Accepted Articlementioning
confidence: 96%
“…5 Additionally, a recent report followed 87 heart transplant recipients in Hubei, finding a low rate of SARS-CoV-2 infection with no severe cases of COVID-19 among them. 19 Interestingly, SOT recipients similarly did not appear to be at particularly increased risk of adverse outcomes in past novel…”
Section: Accepted Articlementioning
confidence: 96%
“…A majority of these patients (96.6%) undertook precautionary measures in the community while 64.4% had self-quarantined at home. The authors also proposed that apart from proper sanitization measures, a difference in ACE2 expression in the lung might exist in presence of immunosuppression explaining lower rates of COVID-19 infection [72]. Another group of patients who might be at risk are those awaiting cardiac transplantation.…”
Section: Covid 19 and Heart Transplantmentioning
confidence: 99%
“…Although there are concerns that transplant recipients may have a more severe clinical course due to their immunosuppression and high rate of comorbid conditions. According to published reports, most of transplant recipients with COVID-19 presented with similar symptoms, laboratory values, imaging, and outcomes to those of immunocompetent patients [16][17][18][19][20]. Review of the clinical courses showed that most of the transplant patients were managed successfully without progression of the disease.…”
Section: Resultsmentioning
confidence: 99%